PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL BERBASIS FLIPBOOK MAKER PADA MATERI GAYA DAN GERAK KELAS IV SDN BAHAGIA 04 - Apri Utami Parta Santi; Gina Maharani Prasetya (Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The background of this research is the lack of enthusiasm of students, feeling bored and lacking understanding of the learning process. The purpose of this research is to develop e-module learning media based on flipbook maker. This study uses the Research and Development (R&D) and development model modified by Sugiyono namely potentials and problems, data collection, product design, design validation, design revision, and product testing. This learning media is subjected to expert validation tests conducted by material experts, media experts and linguists. Then a product trial was carried out with the research subject, namely class IV B students at SDN Bahagia 04. The results showed that the flipbook maker-based e-module media was